Awareness of sexual violence, status of temptation and consent among children experiencing sexual violence - Rahman, Ferdousi; Ahmed, Habib; Ray, Debika; Chowdhury, Md Arifuzzaman; Mahmud, Sohel (Journal of Shaheed Suhrawardy Medical College, 2024)
Background: Worldwide sexual violence in children is a common burning problem irrespective of culture and geographical location. Awareness and temptation status among the victims may signify and influence the establishment of sexual violence. This study was conducted to explore awareness of sexual violence, status of temptation and consent among children experiencing sexual violence with their clinical profile. Methods: This cross-sectional study included 106 victimized children attending the Department of Forensic Medicine and Toxicology and One-stop Crisis Center of Dhaka Medical College, Dhaka Bangladesh between June 2019 and March 2020. Sexual violence, status of awareness and temptation were assessed depending on operational definition. Physical examination was also done. Results for numerical data was expressed as mean ± SD, while categorical was expressed as frequency (number) and percentage (%). Results: Age of the victims was 13.55±4.03 years who were mostly students (68.9%) and resided in urban areas (74.5%). Only 67% female children had awareness of sexual violence. Among the affected victims, 48.1% had given consent and 51.9% were tempted. Most of the sexual violence was carried out by lover (43%) and neighbour (39%). More than three-fourth (78.3%) of the sexual violence occurred at house and during day time (62.3%). Almost one-third victims (34%) had previous sexual experience. Time elapsed between occurrence of violence and physical examination ranged from 2-60 days. Among the female victims, more than 70% had developed breast, while pubic hair was grown in 77.5%. None of the male victim either developed moustache or pubic hair. Conclusion: Lack of awareness is an important factor for occurrence of sexual violence. Temptation also plays a major role in affirming consent to establish a sexual violence. Awareness development in children is essential to prevent sexual violence. J Shaheed Suhrawardy Med Coll 2022; 14(2): 30-34